Next generation optical access networks : technologies and economics - Shahpari, Ali (2015)
The work presented herein, studies Next Generation Optical Access Networks (NG-OAN) economically (e.g. energy consumption) and technologically (e.g. rate, reach and dedicated/shared bandwidth). The work is divided into four main topics: energy efficiency in optical access architectures, novel spectrally efficient Long-Reach Passive Optical Networks (LR-PON), crosstalk impacts in heterogeneous and homogenous access networks and hybrid optical wireless transmissions. We investigate the impact of user profiles, optical distribution network topologies and equipment characteristics on resource sharing and power consumption in LR-PON. To have a clear vision on the energy consumption evolution of each part of NG-OAN, a model is proposed to evaluate the energy efficiency of optical access technologies. A spectrally efficient bidirectional Ultra-Dense Wavelength Division Multiplexing (UDWDM) PON architecture is developed using Nyquist shaped 16-ary quadrature amplitude modulation, offering up to 10 Gb/s service capabilities per user or wavelength. Performance of this system in terms of receiver sensitivity and nonlinear tolerance under different network transmission capacity conditions are experimentally optimized. In bi-directional transmis-sion, using frequency up/down-shifting of Nyquist pulse shaped signal from optical carrier, a full bandwidth allocation and easy maintenance of UDWDM networks as well as reduction of Rayleigh back-scattering are achieved. Moreover, self-homodyne detection is used to relax the laser linewidth requirement and digital signal processing complexity at the optical network unit. Simplified numerical model to estimate the impact of Raman crosstalk of multi-system next generation PONs in video overlay is proposed. Coexistence of considered G.98X ITU-T series and coherent multi-wavelength systems is considered and assessed. Additionally, the performances of bidirectional hybrid optical wireless coherent PONs over different optical distribution network power budgets and hybrid splitting ratios are evaluated.